Diabetes Mellitus Gestational In between Physical Activity and Dietary Habits : A Literature Review - Irma Afifa (Faculty of Medicine, Universitas Negeri Surabaya, 2025)
Gestational diabetes mellitus carries significant risks to the health both of the mother and fetus. Lifestyle modifications, mainly dietary patterns and physical activity, have emerged as major modifiable factors in the prevention and management of GDM. We conducted an analysis of recent meta-analyses, umbrella reviews, and systematic reviews published between 2020 and 2025 that assessed dietary interventions, physical activity programs, and combined lifestyle approaches for GDM prevention and management. Primary outcomes included the incidence of GDM, measures of glycemic control, gestational weight gain, and maternal-neonatal clinical outcomes. Dietary interventions showed consistent protective effects against GDM, with a pooled odds ratio of 0.69 (95% CI 0.56–0.84), or approximately a 31% relative risk reduction. The physical activity effects were significantly modified by timing and intensity: first-trimester initiation (OR 0.57, 95% CI 0.43–0.75) and mild-to moderate intensity activity (OR 0.65, 95% CI 0.53–0.80), while vigorous or later-start exercise did not confer any benefit (OR 1.09, 95% CI 0.50–2.38). Combined diet-plus-exercise interventions may have a possible but inconsistent protective effect, with high heterogeneity across studies. DASH and Mediterranean dietary patterns presented favorable results in pooled comparisons.